EMOTIONS AND SOCIAL TIES IN LATE LIFE: NEW FINDINGS FROM THE DAILY EXPERIENCES AND WELL-BEING STUDY. (11th November 2018) - Huo, M; Fingerman, K
Abstract: Older adults hold strong values for emotions and social ties, which are consistently associated with their well-being. Yet, the mechanisms underlying these associations remain under-investigated. To address this gap, research in this symposium drew on the newly conducted Daily Experiences and Well-being Study. This symposium examines the associations between older adults' social encounters and well-being throughout the day and explore factors influencing these associations. Fingerman and colleagues discuss how older adults' encounters with a variety of social partners may be associated with their physical activity. Birditt and colleagues examine older adults' daily solitude and negative mood, explaining when staying alone may serve as a buffer. Charles and colleagues present older adults' encounters with different social ties and how the network type may shape older adults' emotional experiences. Luong and colleagues assess older adults' valuation of negative affect and how such valuation is associated with these older adults' depressive symptoms. Together, these papers identify variation in older adults' encounters with social partners and reveal immediate physical and emotional outcomes of these encounters. Some older adults interact with diverse social partners throughout the day and benefit from such social integration in a daily context. Yet, for certain older adults who stay alone, such solitude may buffer against conflicts with their social partners. Further, older adults' appraisal and valuation of their emotional experiences play a critical role in how these encounters influence older adults' well-being throughout the day.